Registration of RMPAP‐C4, a Random‐Mated Primitive Race Accession Cotton Germplasm Population. Issue 3 (20th June 2014) - McCarty, J. C.; Jenkins, J. N.; Gutierrez, O. A.; Hayes, R. W.
Abstract : A random‐mated population involving four cultivars of Upland cotton ( Gossypium hirsutum L.) and 30 day‐neutral primitive accessions, RMPAP‐C4 (Reg. No. GP‐980, PI 670133) was developed and jointly released by the USDA–ARS and the Mississippi Agricultural and Forestry Experiment Station in 2014. This population involved five cycles of random mating following the cross of 30 day‐neutral primitive accessions to the conventional cultivars Sure‐Grow 105, DP 393, FM 458, and ST 474. Random mating was facilitated by hand emasculation and bulk pollen methodology. The aim of this project was to incorporate alleles from day‐neutral primitive accessions into a population useful to cotton breeding programs for trait improvement and genetic diversity. The mean values for agronomic traits measured following five cycles of random mating were not significantly different from those of cultivars, except for lint percentage, which was lower. Small nonsignificant changes occurred for fiber quality traits, except for fiber uniformity, which increased following random mating. Morphological trait diversity is also present in this population. This unique population should offer new genetic combinations and genetic diversity that may be useful to Upland cotton breeding programs.